N. G. Chernyshevsky’s survey reviews on historical and geographical works of A. S. Norov - Lyovin, Sergey Vladimirovich (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2022)
A wide range of diverse works represents the scientific, journalistic and literary heritage of N. G. Chernyshevsky. Reviews and surveys of historical works occupy a prominent place among them. The paper attempts to analyse two such surveys on the historical studies of the Minister of Public Education A. S. Norov. The author of the paper concludes that N. G. Chernyshevsky thoroughly reviewed his scientific publications showing a deep knowledge of the issues presented there. N. G. Chernyshevsky’s analytical reviews can be considered as some addition to the problems of A. S. Norov’s works.